2016
DOI: 10.17507/tpls.0604.29
|View full text |Cite
|
Sign up to set email alerts
|

A Contrastive Study of ESP Text Books and Content Books for Metadiscourse Markers: The Cases of Psychology, Medicine, and Mechanical Engineering

Abstract: Abstract-The present study sought to investigate the extent to which discipline specificity of the occurrence of metadiscourse (MD) elements had been taken into account in developing ESP textbooks in Iran. To do so, three distinct disciplines, namely, psychology, medicine, and mechanical engineering were chosen for investigation. For each discipline, two textbooks were analyzed; one content book, and one ESP textbook developed for students in the Iranian academic context. To analyze the six textbooks, Hyland's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…They found that most phrases suggested for taking part in academic speaking events in small groups in three EAP coursebooks did not appear in the laboratory and tutorial corpora they developed. Alibabaee et al (2016) observed that metadiscourse markers, such as hedges boosters, occurred significantly fewer in an EMP coursebook designed by Iranian writers than in a content coursebook written by first language speakers of English. Sznajder's (2010) study revealed a slight overlap between metaphors included in a business English coursebook and those in a business English corpus.…”
Section: Focus and Methods Of Esp And Emp Coursebook Analysismentioning
confidence: 90%
“…They found that most phrases suggested for taking part in academic speaking events in small groups in three EAP coursebooks did not appear in the laboratory and tutorial corpora they developed. Alibabaee et al (2016) observed that metadiscourse markers, such as hedges boosters, occurred significantly fewer in an EMP coursebook designed by Iranian writers than in a content coursebook written by first language speakers of English. Sznajder's (2010) study revealed a slight overlap between metaphors included in a business English coursebook and those in a business English corpus.…”
Section: Focus and Methods Of Esp And Emp Coursebook Analysismentioning
confidence: 90%